1963
DOI: 10.1111/j.1471-4159.1963.tb13671.x
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Distribution of Glycolytic and Tricarboxylic Acid Cycle Enzymes in Rat Brain Mitochondrial Preparations

Abstract: IT WAS recently reported that the non-ionic detergent, Triton X-100, will solubilize over half of the proteins of the mitochondrial fraction obtained from rat whole brain honiogenates (BRUNNGRABER and AGUILAR, 1962). This extract contained several glycolytic as well as tricarboxylic acid cycle enzymes. It is well established that the usual preparation of rat brain mitochondria is a heterogeneous mixture of cell particulates ( HEBB and WHITTAKBK, 1958; WHITTAKER, 1959; DE ROBERTIS et nl., 1962) and that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1966
1966
1977
1977

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Although pyruvate kinase is reported to be a cytoplasmic component in brain as well as in other tissues (JOHNSON, 1960;BRUNNGRABER, AGUILAR and OCCOMY, 1963), we have observed activity in a number of membrane fractions as well. To determine whether this enzyme was indeed associated with membranes, we thought it desirable to study its quantitative distribution in different subcellular fractions.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…Although pyruvate kinase is reported to be a cytoplasmic component in brain as well as in other tissues (JOHNSON, 1960;BRUNNGRABER, AGUILAR and OCCOMY, 1963), we have observed activity in a number of membrane fractions as well. To determine whether this enzyme was indeed associated with membranes, we thought it desirable to study its quantitative distribution in different subcellular fractions.…”
contrasting
confidence: 55%
“…Since pyruvate kinase is mentioned in the literature as being present solely in the cytoplasm of nerve tissue (JOHNSON, 1960;BRUNNGRABER et al, 1963), we thought it advisable to secure further evidence that this enzyme is associated with neural membranes. The enzyme does not appear to be specific for the membranes in any particular subcellular fraction, since all membrane particles tested (microsomes, synaptosomes, mitochondria and synaptic vesicles) exhibited appreciable activity.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria exhibited rapid swelling in 250mosM solutions of ammonium phosphate or ammonium acetate, and in potassium phosphate in the presence of valinomycin and uncoupler, showing that they were capable of normal swelling. Glutamate is, however, metabolized in the mitochondrial matrix, since glutamate is readily oxidized (Brunngraber et al, 1963;Clark & Nicklas, 1970), and we have observed that glutamate is able to stimulate oxidation of malate, presumably by transamination with oxaloacetate in the mitochondrial matrix. Fig.…”
Section: Resultsmentioning
confidence: 58%
“…The histochemical reaction with all three enzyme systems (NADH2-TR, LDH+PMS and LDH-PMS) in unextracted fresh cryostat sections appears partly in the form of small smooth round granules, which could be interpreted as mitochondria. However, LDH is predominantly a cytoplasmic enzyme (see Brunngraber, Aguilar and Occomy, 1963;Johnson and Whittaker, 1963), so the LDH reaction product should not be located in mitochondria-particularly in the presence of the intermediate electron acceptor PMS that circumvents the need for mitochondria1 (or microsomal) " diaphorase ". Moreover, these smooth round granules are not seen in sections extracted with acetone before incubation and it may therefore be inferred that they are lipid droplets.…”
Section: Discussionmentioning
confidence: 99%